STRESS AND JOB SATISFACTION: A CASE SURVEY AMONG NURSES AT HOSPITAL SULTAN ABDUL HALIM, SUNGAI PETANI, KEDAH - Nik Azlina Nik Abdullah; Ismalaili Ismail; Siti Farhana Hasanudin (International Journal of Accounting, Finance and Business, 2023)
The purpose of this study is to examine the relationship between factors of job stress; home-work interference, supervisor support, and workload on job satisfaction. Nurses at Hospital Sultan Abdul Halim, Sungai Petani, Kedah were taken as the respondents in this study. Self-administered questionnaires were used for collection of data. 283 questionnaires were distributed among nurses and the results concluded that there is a significant negative relationship between home-work interference and workload with job satisfaction and supervisor support is having a positive significant relationship with job satisfaction. Several recommendations were put forth in this study for the organization in promoting nurses job satisfaction as well as recommendations for future research.